2019
DOI: 10.1002/mde.3026
|View full text |Cite
|
Sign up to set email alerts
|

To lead or to wait? An application to internationalization strategies under demand uncertainty

Abstract: We examine the exports versus foreign direct investment (FDI) decision under demand uncertainty for an asymmetric cost duopoly. One of the firms can lead entry before demand realization or retain flexibility enjoying an informational advantage. When the time value of information is small and for sufficiently low investment costs, follow‐the‐leader behavior in FDI arises. Relatively high investment (fixed) costs result in follow‐the‐leader exporting behavior. When the time value of information becomes significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Spencer and Brander (1992) present a duopoly model with uncertainty in demand where one firm has exogenously been given the possibility to commit the quantity before the realization of the uncertainty, taking advantage of moving first and acting as a Stackelberg leader; or defer its decision till the uncertainty is resolved, thereby losing its leading role but allowing her to adjust output. Their paper can be extended to apply the dichotomy pre-commitment versus flexibility to the internationalization strategies of heterogeneous firms (Barac & Moner-Colonques, 2019). It can be shown that follow-the-leader behaviour in FDI happens when setup costs are small and demand uncertainty is low enough.…”
Section: Further Extensions and Robustnessmentioning
confidence: 99%
“…Spencer and Brander (1992) present a duopoly model with uncertainty in demand where one firm has exogenously been given the possibility to commit the quantity before the realization of the uncertainty, taking advantage of moving first and acting as a Stackelberg leader; or defer its decision till the uncertainty is resolved, thereby losing its leading role but allowing her to adjust output. Their paper can be extended to apply the dichotomy pre-commitment versus flexibility to the internationalization strategies of heterogeneous firms (Barac & Moner-Colonques, 2019). It can be shown that follow-the-leader behaviour in FDI happens when setup costs are small and demand uncertainty is low enough.…”
Section: Further Extensions and Robustnessmentioning
confidence: 99%